Myocardial ischaemia in cardiac amyloidosis: a change of perspective. (3rd October 2022) - Ioannou, A; Chacko, L; Kotecha, T; Patel, R K; Razvi, Y; Porcari, A; Venneri, L; Martinez-Naharro, A; Knight, D; Brown, J; Hawkins, P N; Gillmore, J D; et al.
Abstract: Introduction: Cardiac involvement is the main driver of clinical outcomes in systemic amyloidosis; however many clinical observations are not explained by the concept of replacement of the interstitium by amyloid material. Preliminary studies support the hypothesis that myocardial ischaemia contributes to cellular damage. Purpose: This study assesses the presence and mechanisms of myocardial ischaemia using cardiovascular magnetic resonance (CMR) with multiparametric mapping and histopathological assessment. Methods: Ninety-two patients with cardiac amyloidosis (CA) (AL = 41, ATTR = 51) and 97 without CA (3-vessel coronary disease (3VD) = 47, unobstructed coronary arteries = 26, healthy volunteers (HV) = 24) underwent quantitative stress perfusion CMR with myocardial blood flow (MBF) mapping. Twenty-six myocardial biopsies and 3 explanted hearts with CA were analysed histopathologically. Results: Stress MBF was severely reduced in patients with CA with lower values than patients with 3VD, unobstructed coronary arteries and HV (CA = 1.03±0.51 ml/min/g, 3VD = 1.35±0.50 ml/min/g, Unobstructed coronaries = 2.92±0.52 ml/min/g, HV = 3.14±0.69 ml/min/g; CA vs 3VD p=0.008, CA vs Unobstructed coronaries p<0.001, CA vs HV p<0.001). After adjustment for intracellular volume the MBF in patients with CA remained significantly lower than in HV (stress MBF/ICV: AL = 2.24±1.12, ATTR = 2.22±0.93, HV = 4.38±1.06; AL vs. ATTR p=1.000, AL vs HV p<0.001, ATTR vs. HV p<0.001). Myocardial perfusion reserve (MPR) was severely reduced in CA patients, compared to HV and patients with unobstructed coronary arteries, with the degree of reduction being comparable only to patients with 3VD (CA = 1.55±0.60, 3VD = 1.54±0.51, unobstructed coronaries = 2.78±0.70, HV = 4.08±0.86; CA vs 3VD p=1.000, CA vs unobstructed coronary arteries p<0.001, CA vs. HV p<0.001). Myocardial perfusion abnormalities correlated with amyloid burden, systolic and diastolic function, structural parameters and blood biomarkers (p<0.05). Biopsies demonstrated diffuse hypoxia with abnormal VEGF staining in cardiomyocytes and endothelial cells. Amyloid infiltration in intramural arteries was associated with severe lumen reduction in 20% of vessels, and severe reduction in capillary density. Conclusion: CA is associated with severe myocardial ischaemia demonstrable by histology and CMR stress perfusion mapping. Histological evaluation indicates a complex pathophysiology, where systolic and diastolic dysfunction, amyloid infiltration of the epicardial arteries and disruption and rarefaction of the capillaries play a role in contributing to myocardial ischaemia. Funding Acknowledgement: Type of funding sources: None.